Citizens', Scientists', and Policy Advisors' Beliefs about Global Warming. Issue 1 (March 2015) - Bolsen, Toby; Druckman, James N.; Cook, Fay Lomax
Numerous factors shape citizens' beliefs about global warming, but there is very little research that compares the views of the public with key actors in the policymaking process. We analyze data from simultaneous and parallel surveys of (1) the U.S. public, (2) scientists who actively publish research on energy technologies in the United States, and (3) congressional policy advisors and find that beliefs about global warming vary markedly among them. Scientists and policy advisors are more likely than the public to express a belief in the existence and anthropogenic nature of global warming. We also find ideological polarization about global warming in all three groups, although scientists are less polarized than the public and policy advisors over whether global warming is actually occurring. Alarmingly, there is evidence that the ideological divide about global warming gets significantly larger according to respondents' knowledge about politics, energy, and science.